Applying Accompany Model for the Cultural Development of Bunun and Siraya Tribes - Peng, Li-Hsun; Hsueh, Chia-Hsin (The European Journal of Multidisciplinary Sciences, 2016)
Taiwanese aboriginal cultures have been lightly valued. This study attempts to use the Accompany Model to help the aborigines of the Bunun and Siraya tribes develop their cultural identity. It establishes the design system through education to develop the local aborigines’ traditional craft art, and to advance how the tribes learn and grow together through creative workshops. The Post-Colonialism, Cultural Identity, and Narratology theories were adapted to reach a deeper interaction by “accompanying” aborigines. This not only builds their self-identity but also allows for an understanding of their culture through In-Depth Interviews and Long-Term Participation. Several design projects for the Bunun tribe were created by the researchers who volunteered to initiate creative activities for the Siraya tribe in recent years. This was in response to the growing need to generate a deeper intercultural knowledge of the aboriginal cultural and creative industry in order to preserve their cultural elements for the younger generation and the public. Overall, this research, through a literature review and information about the current status of the investigation and enforcement, focuses on link design, story, and culture integration. This research was undertaken to help the aborigines in Taiwan recognize and value their multicultural heritage. In conclusion, the cultivation of a new aboriginal identity will achieve ethnic harmony locally and globally.